Exploring Principals’, Teachers’, And Students’ Perceptions Of Public Speaking Practices At Public Schools In Baku - Dadashova, Gulnar; Aghazada, Sama; Yusifova, Sevinj (ADA University, 2023)
This research examines the perceptions of students, teachers, and school principals regarding the importance of public speaking practices in public schools in Baku. It also explores potential actions that school principals can take to raise awareness about these practices. The research participants are three school principals, eight Azerbaijani and Language teachers and 22 students from 6th to 9th grade. Semi-structured interviews are conducted with school principals, and focus group discussions are carried out with teachers and students. The study examines the students', teachers’ and principals’ viewpoints on the relevance of public speaking skills in students' current and future lives, particularly in terms of their careers and effective communication. The findings indicated that students encounter difficulties such as panic, anxiety, fear of failure, word confusion, and shyness when speaking in public. Furthermore, the research provides suggestions which are given from students, teachers, and school principals to raise awareness on public speaking practices in public schools. The study highlights the significance of extracurricular activities such as public speaking clubs, oral competitions, and discussions on movies or books. By incorporating these activities into the school curriculum, students can enhance their public speaking abilities. Considering the findings of the study, a workshop called “Public speaking strategies and assessment criteria” has been conducted at one of the public schools in which the data was gathered. The purpose of this workshop was to increase awareness among principals, teachers, and students regarding the importance of public speaking practices by providing participants essential public speaking strategies and offer Azerbaijani Language and Literature teachers guidance on evaluating students' proficiency in various public speaking techniques.
Keywords: Public speaking -- Study and teaching -- Azerbaijan; Communication skills -- Education; Extracurricular activities -- Educational aspects; Education